Development of Criminal Policy in Hungary during the First Decade of the 21st Century (Archives of Criminology, 2008)
The article describes the changes in the state’s reaction to crime that was supplemented in 2003 and resulted in creatingthe National strategy for community crime prevention (2003), the Institutions for helping the victims of crimes (2005), and the Introduction of mediation into criminal justice (2006). The changes were based on a new approach of criminal policy requiring that crime be seen as a complex social phenomenon, not simply a legal problem. The National Strategy for Community Crime Prevention stresses that in each community measures for curbing the effects of crime, addressing victimisation, and reducing opportunities for crime shall be applied simultaneously. The author presents the tasks entrusted to the Victim Support Services: disseminating information, promoting the enforcement of interests, providing legal support from legal specialists, and distributing immediate financial assistance and compensation. The author also describes the modification to the Hungarian Penal Code that was implemented in 2006, introducing mediation as an institution of restorative justice. Since January 2007 crimes against a person or property, as well as traffic crimes previously punished with no more than three years’ imprisonment, cannot result in punishment if the perpetrator has reimbursed the injured party for the damages through mediation, or made good for the harmful consequences of the crime in any other way. In the case of crimes belonging to the above-mentioned categories, but punishable by five years’ imprisonment, if the damages were compensated, then the punishment may be reduced or even lifted completely.